Dynamic mathematical model as a tool for detecting and preventing school violence: a case report - Hernando, Inmaculada; Sanz, Roberto; Moreno-Latorre, Esther (Frontiers in Education, 2023)
Coexistence is an essential factor that influences educational quality. School violence problems affect a large number of students, conditioning their personal and academic future. The aim of this study was to present a different study tool that would allow the optimization of the factors that influence classroom climate, establish mechanisms to detect and predict how the modification of these factors can positively or negatively affect it, and determine the most appropriate way of intervention before it occurs. Dynamic mathematical models are a complex tool that allows us to study a given problem or reality in real time and develop predictive instruments, through the analysis of mathematical relationships, allowing us to adapt the answers in a personalized way. In this paper, an example in which the measure of the classroom climate throughout an academic course in a supposed situation, is implemented. It consists of a dynamic mathematical model developed with Stella 10 software using only some of the variables that affect classroom climate, which are distributed in two sections: on the one hand, one psychological that includes Rabies Level and Isolation Level due to loss of self-esteem, and on the other hand, one physical that includes the number of aggressive students and total number of physically assaulted students. Since the climate classroom is very complex, other variables or a greater number of them could have been used in this hypothetical case; however, the example explains how this kind of model works and shows the great utility that it can have in this type of study. Regarding the most significant benefits that this tool can bring us, some stand out. On the one hand, we can adapt the instrument to the specific characteristics of the class group, introducing or eliminating the variables depending on their relevance to the problem at hand. On the other hand, this versatile tool not only adapts to the reality of the classroom but also to the specific moment in which the students are. The greatest limitation is the large quantity of information required to adjust the model to reality.